Ukrainian early (pre‐1850) historical weather observations. (12th October 2020) - Skrynyk, Oleg; Luterbacher, Jürg; Allan, Rob; Boichuk, Dmytro; Sidenko, Vladyslav; Skrynyk, Olesya; Palarz, Angelika; Oshurok, Dmytro; Xoplaki, Elena; Osadchyi, Volodymyr
Abstract: In this paper, we describe the results of a climate data rescue (DARE) activity conducted at the Ukrainian Hydrometeorological Institute (Kyiv, Ukraine) in cooperation with the Justus Liebig University Giessen (Giessen, Germany), the World Meteorological Organization (WMO) and Met Office Hadley Centre (Exeter, United Kingdom). The focus of our work is on pre‐1850 sub‐daily meteorological observations conducted on the territory of modern Ukraine. Data from eight stations (stored in special hard copy tables/books, with handwritten records) have been digitized during the DARE process, resulting in 291, 103 rescued values in total. More than half of this number (165, 980, 57%) are related to air temperature data, 124, 376 data values ( 42.7%) concern atmospheric pressure records and 747 values ( 0.3%) are precipitation data. Simple quality control of the digitized data has been conducted, including an intercomparison between stations as well as comparison with monthly temperature data previously digitized from other paper sources. The quality control procedures revealed fairly good agreement between rescued time series on the monthly time scale as well as with the monthly data from independent sources. However, several periods for a few stations should be used with caution due to relatively large discrepancies that were found. The rescued digital database can be used for extreme value analysis for the pre‐1850 period in comparison with today's climate, regional climatological studies and will be used for future Reanalysis. In addition, for the first time, we show that subdaily temperature from Kyiv during 'the year without summer' 1816 in Western and Central Europe were not anomalous in this part of Eastern Europe. Abstract : Data of pre‐1850 sub‐daily meteorological observations (mainly air temperature and atmospheric pressure) made at eight meteorological stations located on the territory of modern Ukraine are presented. The rescued dataset can be used for different meteorological and climatological purposes and can be considered as an important supplement to existing digitized archives of original meteorological measurements performed in the first half of 19th century.